Special Autonomy Law and Education Attainment in West Papua: A Quasi-Experiment Analysis - Tiara Ariyanda; Devita Arifyani (Jambura Equilibrium Journal, 2020)
West Papua was granted Special Autonomy status in 2008 as mandated by Government Regulation No.1/2008. Special Autonomy Law has granted more or less than 30 percent of education Special Autonomy Funds for West Papua. Thus, this study evaluates the impact of Special Autonomy Law on education attainment in Indonesia. We use panel data sets of 33 regions in Indonesia that covers the period of 2001 to 2018. We employ quasi-experiment analysis, specifically the Difference-in-difference (DID) analysis in evaluating before and after effect of Special Autonomy Law in West Papua. We further develop fixed-effect model (FEM) panel data analysis in understanding the impact of Special Autonomy Law on education by controlling socioeconomic and demographic variables. DID analysis in this study suggests that Special Autonomy Law appears to worsen education attainment in West Papua. This study further found that despite positive and significant effect of education spending share on education attainment, it appears that the realization of education spending in West Papua is relatively low. Keywords: Special Autonomy Law, Education Attainment, Education Spending Share, DID, FEM